2015
DOI: 10.5796/electrochemistry.83.861
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Electrochemical Properties of Intercalated Metal–Organic Framework Electrode Materials by Controlling Crystal Growth

Abstract: The growth of the crystal surface of an intercalated metal-organic framework (iMOF) electrode material, 2,6-naphtalnene dicarboxylate dilithium, which forms an organic-inorganic layered structure, was controlled by selecting the solvent species during synthesis. The crystals synthesized under an aqueous solution exhibited a small reversible capacity because the crystal plane in the horizontal direction relative to the layered structure, grew dominantly and exhibited poor lithium intercalation kinetics. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Material properties such as the electrode morphology 49 and shape of crystallites 50,51 of the active material may have a considerable effect on mass and electron transport of the electrode and thereby its electrochemical performance. In addition, it has been shown that particle pulverization can take place and is detrimental to the electrochemical performance of organic electrode materials.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Material properties such as the electrode morphology 49 and shape of crystallites 50,51 of the active material may have a considerable effect on mass and electron transport of the electrode and thereby its electrochemical performance. In addition, it has been shown that particle pulverization can take place and is detrimental to the electrochemical performance of organic electrode materials.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The redox reaction can be improved by controlling the crystal orientation by heat treatment 20 and controlling the crystal plane using synthetic solvents. 22 The hybrid capacitor with 2,6-Naph(COOLi) 2 and activated carbon as the negative and positive electrodes, respectively, exhibits a high-energy density of approximately 60 Wh L −1 , highpower density, and good cyclability 21 .…”
mentioning
confidence: 99%
“…200 mAh g -1 of active material. This drop in capacity is commonly observed for lithium carboxylates, and is normally ascribed to a combination of SEI layer formation, dissolution of active material into the electrolyte or structural changes in the material [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Compared to other carboxylates, dilithium 2-aminoterephthalate 3 can be considered to cycle stably.…”
Section: Resultsmentioning
confidence: 99%